Oxidative stress markers in hypertensive states of pregnancy: preterm and term disease - Kurlak, Lesia O.; Green, Amanda; Loughna, Pamela; Broughton Pipkin, Fiona (Frontiers in Physiology, 2014)
Discussion continues as to whether de novo hypertension in pregnancy with significant proteinuria (pre-eclampsia; PE) and non-proteinuric new hypertension (gestational hypertension; GH) are parts of the same disease spectrum or represent different conditions. Non-pregnant hypertension, pregnancy and PE are all associated with oxidative stress. We have established a 6 weeks post-partum clinic for women who experienced a hypertensive pregnancy. We hypothesized that PE and GH could be distinguished by markers of oxidative stress; thiobarbituric acid reactive substances (TBARS) and antioxidants (ferric ion reducing ability of plasma; FRAP). Since the severity of PE and GH is greater pre-term, we also compared pre-term and term disease. Fifty-eight women had term PE, 23 pre-term PE, 60 had term GH and 6 pre-term GH, 11 pre-existing (essential) hypertension (EH) without PE. Limited data were available from normotensive pregnancies (n=7) and non-pregnant controls (n=14). There were no differences in postpartum TBARS or FRAP between hypertensive states; TBARS (P=0.001) and FRAP (P=0.009) were lower in plasma of non-pregnant controls compared to recently-pregnant women. Interestingly FRAP was higher in preterm than term GH (P=0.013). In PE and GH, TBARS correlated with low density lipoprotein (LDL)-cholesterol (P=0.036); this association strengthened with inclusion of EH ((P=0.011). The 10 year Framingham index for cardiovascular risk was positively associated with TBARS (P=0.003).Oxidative stress profiles do not differ between hypertensive states but appear to distinguish between recently-pregnant and non-pregnant states. This suggests that pregnancy may alter vascular integrity with changes remaining 6 weeks postpartum. LDL-cholesterol is a known determinant of oxidative stress in cardiovascular disease and we have shown this association to be present in hypertensive pregnancy further emphasizing that such a pregnancy may be revealing a pre-existing cardiovascular risk.